2020
DOI: 10.1002/poc.4060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water on excited‐state double proton transfer in 7‐azaindole‐H2O complex: A theoretical study

Abstract: The dynamics of excited‐state double proton transfer (ESDPT) depending on hydrogen bonding of water molecules to the mediating water were studied at the TD‐M06‐2X/6‐31+G(d, p) level. The additional H‐bonding accepting (aW) or donating (dW) water had an effect on the mechanism of ESDPT. The double proton transfer occurred in an asynchronous but concerted protolysis or solvolysis pattern dependence on the aW or dW, respectively. The aW or dW stabilized the corresponding protolysis or solvolysis mechanism, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, as is well known, IR vibrational spectra should be a reasonable mean to ensure structural stability and to probe into hydrogen bonding interactions. [ 38–49 ] In this work, all the simulations about IR spectra for HBT‐Cz systems in solvents reveal that there are no imaginary frequencies for all the related structures. In addition, the IR vibrational frequencies of OH stretching vibrational mode involved in intramolecular OH···N of HBT‐Cz‐enol have been shown in Figure 2, which could provide the clear‐cut signature of excited‐state hydrogen bonding interactions.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, as is well known, IR vibrational spectra should be a reasonable mean to ensure structural stability and to probe into hydrogen bonding interactions. [ 38–49 ] In this work, all the simulations about IR spectra for HBT‐Cz systems in solvents reveal that there are no imaginary frequencies for all the related structures. In addition, the IR vibrational frequencies of OH stretching vibrational mode involved in intramolecular OH···N of HBT‐Cz‐enol have been shown in Figure 2, which could provide the clear‐cut signature of excited‐state hydrogen bonding interactions.…”
Section: Resultsmentioning
confidence: 65%
“…Furthermore, as is well known, IR vibrational spectra should be a reasonable mean to ensure structural stability and to probe into hydrogen bonding interactions. [38][39][40][41][42][43][44][45][46][47][48][49] In this work, all the simulations about IR spectra for HBT-Cz systems in solvents reveal that there are no imaginary frequencies for all the related structures. In addition, the IR vibrational frequencies of O H stretching vibrational mode involved in intramolecular O HÁÁÁN of HBT-Czenol have been shown in Figure 2 226.78 cm À1 for TOL, 230.32 cm À1 for CCl 4 , and 240.53 cm À1 for HEX) between S 0 and S 1 states further reflects that large redshift resulting from low solvent polarity plays the more important role in facilitating excited state reaction for HBT-Cz system.…”
Section: Dimethylsulfoxide [Dmso] Acetone [Ace] Tetrahydrofuran [Thf]...mentioning
confidence: 95%
“…[9,10] Over the years, there are numerous studies by theoretical as well as experimental methods to explore the hydrogen bonding interaction. [11][12][13][14][15][16][17][18][19][20][21] In general, hydrogen bonding can be defined as the interaction between a proton donor and proton acceptor atom (such as X-HÁÁÁY), and both proton donor and acceptor atoms are usually electronegative atoms. [22] For example, the pyridyl nitrogen, carbonyl oxygen, or azole-nitrogen group act as the acceptor of the proton, whereas the amino, hydroxyl, and occasionally pyrrolic groups serve as proton donor groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since then, the ESIPT phenomenon has become a hot research field of many research groups. [2][3][4][5][6][7][8][9][10][11][12][13] Along with the deepening of research, people found that the ESIPT process was one of the most general and fundamental process in biological and chemistry systems. [14][15][16][17][18][19][20] The ESIPT has been widespread applied in many fields such as molecular sensors, molecular date storage, molecular switches, microenvironment probe, radiation hard scintillators, developments of ultraviolet stabilizers, and luminescent materials.…”
Section: Introductionmentioning
confidence: 99%